The protection of the state secret in the legal history of Europe - GÁL, István László (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
The legal regulation of the protection of the state secret have appeared relatively late in European legal history over the last two centuries. The secrecy provisions have always been in accordance with the standards of the given age, in most cases relatively neutral regulations, and a certain development arc can be observed. It can be seen in the gradual modernization of the rules and, on the other hand, in the increase in the number of guarantee elements from the end of the socialist era. With regard to criminal law, there is a tendency for criminal offenses regarding to state to gradually less and less severe. The various rules of state secrecy and related crimes has eased in most European countries’ criminal law regulation since 1989.
Keywords: secret; state secret; classified data; Code Csemegi; perduellio; Evidenzbureau; State Protection Authority; classification